Peningkatan Prestasi Belajar Melalui Strategi Pembelajaran Kooperatif Tipe Team Assisted Individualization (TAI) Mata Pelajaran IPS Siswa Kelas III SDN Kalianget Barat II Kab. Sumenep - Tri Sutrisno (ENTITA: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2020)
This research aims to; Want to know an increase in social studies learning achievement after the implementation of cooperative learning model Teams Assisted Individualization class III students of SDN Kalianget Barat II Kab. Sumenep "; Want to know the effect of motivation to study social studies after the implementation of cooperative learning model Teams Assisted Individualization class III students SDN Kalianget Barat II Kab. Sumenep ", provides an overview of appropriate learning methods in an effort to improve student achievement and make students become active in teaching and learning activities. In this study using a class action research design (CAR). The design of the classroom action research was chosen because (1) the study of classroom context research was carried out by the teacher to solve social studies learning problems, because the third grade students of SDN Kalianget Barat II Regency. Sumenep still experiencing difficulties in achievement especially social studies subjects, has not found the right learning strategy. Based on the results of the research that has been presented for three cycles, the results of the entire discussion and analysis that have been carried out can be concluded as follows; The TAI model of cooperative learning methods can improve the quality of social studies learning; The TAI model of cooperative learning method has a positive impact in increasing student achievement which is marked by an increase in student learning completeness in each cycle, namely cycle I (68.42%), cycle II (81.58%), cycle III (94.74% ).